Analisis Peran Kepolisian Resor Sikka dalam Mengurangi Kasus Pencurian Kendaraan Roda Dua di Kota Maumere - Maria Felisitas Isna Lodang; Adrianus Djara Dima; Darius Antonius Kian (International Forum of Researchers and Lecturers, 2024)
The objectives of this research are: 1. To determine the role of the Sikka resort police in reducing cases of two-wheeled vehicle theft in the city of Maumere. 2. To find out the factors that hinder the success of the Sikka resort police in reducing cases of two-wheeled vehicle theft in the city of Maumere. The type of research used by researchers is empirical legal research. It is oriented towards primary data (field research results). The results of the research show that 1. The Sikka Resort Police carries out various important roles, namely: receiving complaints from the public, carrying out investigations, which are then followed by delegation files to the public prosecutor to be forwarded during the examination of the case in court. In their preventive role, the Sikka Resort Police do this by holding activities such as certain operations, selective raids, guarding, police patrols and routine patrols. Meanwhile, the repressive role of the Sikka Resort Police takes action jointly with the prosecutor's office and the court in imposing criminal sanctions. 2. Factors that hinder the Sikka Resort Police in dealing with criminal acts of motor vehicle theft include the public being late in reporting, the perpetrator running away, the reporter not knowing who committed the theft, the reporter having no witnesses, evidence (no CCTV), vehicle without keys, lack of evidence and evidence, difficulties when searching for lost vehicles because they are still carrying out manual checks.